The effect of water storage and humidity on the incidence of dengue hemorrhagic fever in the work area of the Kebayakan Health Center, Central Aceh Regency - Zulfikar Zulfikar; Ririh Yudhastuti; Setya Haksama; Idawati Idawati; Kartika Kartika; Muzaffar Muzaffar; Maulina Iriyanti; Mawadhah Yusran; Elyarianti Elyarianti (AOSIS, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is an acute febrile disease found in the tropics with a geographic distribution like malaria. Dengue fever is spread to humans by the Aedes aegypti mosquito. More than 100 tropical and subtropical countries have experienced dengue eruptions and dengue hemorrhagic fever; approximately 50,000 cases each year are hospitalized, with thousands of people dying. Objective: This study aims to determine the effect of water storage and humidity on the incidence of Dengue Hemorrhagic Fever (DHF) in the work area of the Kebayakan Health Centre, Central Aceh Regency. Materials and Methods: This research is an analytic survey research with a case-control research design. In this case, there were 55 DHF patients consisting of children and the elderly as respondents. Controls were 55 DHF patients consisting of children and the elderly. The analysis used a chi-square test. Result: The results showed that the factors that significantly affected the incidence of DHF were humidity (P=0.002 OR=4.571 95% CI=1.752-11928) and water reservoirs (P=0.004 OR=3.328 95% CI=1.521-7.282). Conclusions: it is hoped that the community will participate in efforts to eradicate dengue hemorrhagic fever (PSN-DHF), and water reservoirs should be cleaned at least once a week to prevent the presence of mosquito larvae and pay more attention to environmental sanitation.